Migrant networks, regional development and internal migration flows in Brazil - Ana Carolina Borges Marques Ribeiro; Silvio H. T. Tai (EconomiA, 2023)
Purpose: This study analyzes the role of migrant networks in the migration flows in relation to the educational level of the migrants and economic growth of the states of origin and destination in Brazil. Design/methodology/approach: Fixed effects estimator applied to microdata. Findings: The results show migrant networks have a significant and positive impact on migration flows of the different educational levels. The economic growth in the destination state accentuates this effect, while the economic growth in the origin state has distinct impacts according to the educational level of the new migrant. Originality/value: The authors investigate the importance of migrant networks in the internal immigration within a developing country with large internal movement of people. In Brazil, the socio-economic condition of the population varies considerably in relation to its geography, which explains the country's large internal migration flows.
Keywords: 330; Economic growth; Brazil; Education level; Migrant flows; Migrant networks